Reconstructing a Heavy Neutral Lepton at the LHC - Pablo de la Torre; Manuel Masip; Fuensanta Vilches (Journal of High Energy Physics)
Abstract Heavy lepton singlets N slightly mixed with a standard neutrino ν ℓ are usually searched for at the LHC in the trilepton plus p T miss $$ {p}_{T}^{miss} $$ channel: pp → W + → ℓ + N with N → ℓ − W + → ℓ − ℓ′ + ν. We show that, although the longitudinal momentum of the final ν escapes detection, the mass of the heavy lepton can be reconstructed. While this possibility has not been considered in recent LHC searches, we find that the search for a mass peak could improve the current collider bounds on the mixing |V ℓN |2 for any mass m N ≥ M W .